1976
DOI: 10.3382/ps.0551615
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Affecting Plasma Amino Acid Patterns in Chickens Fed Practical and Purified Diets

Abstract: Experiments were conducted to investigate plasma free amino acid concentrations in the chick. After one hour of fasting, total plasma amino acid concentration decreased to approximately half of the full-fed value. Within three to six hours, most amino acids had returned toward the full-fed level but did not exceed it throughout a 48 hour period of starvation. However, after 48 hours fasting lysine, threonine, and isoleucine accumulated three-fold, two-fold and two-fold of the full-fed level, respectively. Seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…(60 d.p.m./#1), with or without the addition of BCAA or all amino acids other than methionine at plasma concentrations [8,15]. In all of these experiments, one muscle was used for the control while the contralateral muscle was used for the treatment.…”
Section: Vol 257mentioning
confidence: 99%
“…(60 d.p.m./#1), with or without the addition of BCAA or all amino acids other than methionine at plasma concentrations [8,15]. In all of these experiments, one muscle was used for the control while the contralateral muscle was used for the treatment.…”
Section: Vol 257mentioning
confidence: 99%
“…In experiments designed to measure the amounts of alanine, glutamate, glutamine and tyrosine in the muscle proteins, in the intracellular free pool and released to the incubation media, EDC muscles were incubated in the basal medium containing 12 mM-glucose as described above. In experiments designed to determine the effect of pyruvate and ketone bodies on amino acid metabolism, the basal media contained 12 mM-glucose, 0.5 mMleucine, 0.5 mM-valine, and all other amino acids at plasma concentrations [26], except for alanine, glutamine, glutamate, tyrosine and histidine, which were absent (medium B). Medium B containing either 0 or 12 mMglucose was used in studies of the effect of glucose on amino acid metabolism.…”
Section: Measurement Of the Release Of Glutamate Glutamine And Alanimentioning
confidence: 99%
“…Consequently, this study further demonstrated that central NPY altered the utilization of metabolic fuels from carbohydrates to lipids/proteins. Therefore, the reduction in plasma amino acid concentrations observed in all NPY-treated groups in the present study was likely due to the accumulation of protein synthesis rather than to the gluconeogenic phenomenon observed in chicks during starvation ( Maruyama et al ., 1976 ). White et al .…”
Section: Discussionmentioning
confidence: 66%